Respuesta :

[tex]\bf \textit{Logarithm Change of Base Rule} \\\\ log_a b\implies \cfrac{log_c b}{log_c a}\\\\ -------------------------------\\\\ log_{0.5}(15)=1-2x\implies \cfrac{log_{10}(15)}{log_{10}(0.5)}=1-2x \\\\\\ 2x=1-\cfrac{log_{10}(15)}{log_{10}(0.5)} \implies x=\cfrac{1-\frac{log_{10}(15)}{log_{10}(0.5)}}{2} \\\\\\ x=\cfrac{1}{2}-\cfrac{log_{10}(15)}{2log_{10}(0.5)}[/tex]

keeping in mind that for the change of base rule, it doesn't matter what the base "c" is, so long is the same above and below.

According to the Logarithm change of base formula,solution will be

             [tex]\rm X=\dfrac{1}{2}-\dfrac{ \log_{10} 15}{\log_{10} 0.5}[/tex]

To solve the given question we need to understand change base rule of logarithm.

What is Logarithm Change of Base Rule?

         [tex]\rm \log_{a} b= \dfrac{ \log_{c} b}{\log_{c} a} \;\;\;\;\;\;\;\;\;[/tex]  

where, we say Log b base a          

Given :   [tex]\rm \log_{0.5} 15=1-2x[/tex]

               [tex]\rightarrow\;\; \dfrac{\log_{10} 15}{\log_{10} 0.5}\\\\ \;\;\;\;\;\; \; \rm 1-2x[/tex]

               [tex]\rm 2x=1-\dfrac{\log_{10} 15}{\log_{10} 0.5}\\\\x=\dfrac{1-\dfrac{\log_{10} 15}{\log_{10} 0.5}}{2}\\\\\\x=\dfrac{1}{2}-\dfrac{\log_{10} 15}{2 \log_{10} 0.5}[/tex]

Always remember Log base value will always be Positive.Log cannot be negative.

Learn more about Logarithm here : https://brainly.com/question/24788069

ACCESS MORE